Effect of Strategy Implementation on Access to Water in Kisumu County, Kenya - Okwara, Benjamin Onyango; Onditi, Alvin Lucy; Were, Pamela; Monari, Fronica (International Journal of Research and Innovation in Social Science (IJRISS), 2024)
Strategy implementation is a sub-process of strategic management and has been said to improve access to goods and services ‘It involves the actualization and translation of plans into action. This study focused on the effect of strategy implementation on access to water in Kisumu county Kenya. Kisumu County was selected as the venue of the study because it hosts the third largest fresh water lake in the world and yet experiences problems of access to good quality water. The study employed an explanatory research design that focused on quantitative approach and was supported by the qualitative approach. The units of analysis were strategy interpretation, organization structure and leadership. The target population was 205 respondents. A sample size of 134 respondents were selected using a combination of purposive and stratified sampling techniques. Data was collected using questionnaires and document analysis guides. Validity of the instruments was established through expert vetting while reliability was established through piloting, using the test -retest method which yielded a reliability coefficient of .72. Results indicated that strategy implementation had a positive significant relationship with access to water, implying that effective and efficient strategy implementation will lead to efficient and effective access to water. Based on this finding it’s recommended that the water utility should treat and test water in springs and boreholes to increase access to quality improved waters. Kisumu Water and Sewerage Company Limited ( KIWASCO) should also develop facilities for raw and processed water storages. Every house-hold should have water storage of at least 4500 litres as recommended by Government policy. KIWASCO should use geographical product structure in order to expand water services in every area and improve product content, increase uses of water technology to reduce reliance on natural springs and streams which provide unprocessed water.
Keywords: Effect; Strategy Implementation; Access to Water